BOOK REVIEW: Alexandru Ciocîltan, „Comunitățile germane de la sud de Carpați în Evul Mediu (secolele XIII-XVIII)” [“The German Communities from South of the Carpathians in the Middle Ages (13th-18th Centuries)”], Brăila, Editura Istros a Muzeului Brăilei, 2015, 517 p., ISBN: 978-606-654-121-3 - ȘTEFAN, Andrei-Alexandru (Studia Universitatis Babeș-Bolyai Historia, 2017)
The result of a daring doctoral research, Alexandru Ciocîltan’s volume contributes to the historiographical debate through a subject less familiar to the Romanian historical writing, though very rich in first-hand sources – the history of an ethno-confessional community surveyed throughout its entire existence, which had lasted for about five centuries. Put under the sign of several paradigms of historical research – covering local, minority or urban perspectives – the present work is a genuine milestone in this historian’s career, more and more specialized in decrypting the medieval and early-modern history of the German communities in Wallachia. The particularity of the subject allowed the author to undertake a rather exponential approach throughout the seven chapters of his book, which resulted in a linear yet convincing historical monograph, sometimes strongly polemic and demanding when confronting historiographical blunders. In this regard, Ciocîltan resorted to the latest contributions of present-day historians, without ignoring the previous and more or less valuable works, to the results of older or newer archaeological excavations, but also to a multitude of written sources of diplomatic and epigraphic nature, chronicles or reports of Catholic missionaries. From this point of view, perhaps the biggest problem faced by the less-initiated reader in the space, the periods and the themes under scrutiny, is the absence of a critical and broad survey of the primary sources in a distinctive part of this work, afar from the few such aspects mentioned in the introduction.